2005
DOI: 10.1051/radiopro:2005s1-028
|View full text |Cite
|
Sign up to set email alerts
|

Does uranium exposure induce genotoxicity in the teleostean Danio rerio? First experimental results

Abstract: Abstract. Zebrafish were exposed to different concentrations of waterborne uranium (0, 20, 100 and 500 µg U.L -1 ) and were sacrificed for blood sampling after different exposure periods (12h, 36h, 72h, 5, 10 and 20 days) in order to assess DNA integrity in erythrocytes, using the comet assay and flow cytometry. Concurrently, uranium bioaccumulation was studied in the remaining tissues to understand the potential genotoxic biomarker responses. Both genotoxic assays revealed significant effect of waterborne ura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 9 publications
1
23
1
Order By: Relevance
“…But when we adjust the deb model with the one compartment toxico-kinetic module to whole body residues provided in Barillet et al (2005) and Barillet et al (2011), we see that at 2100 nM U, uptake should be very important but it hardly is compared to predictions ( fig. 8C).…”
Section: Adult Whole Body Residuesmentioning
confidence: 99%
See 4 more Smart Citations
“…But when we adjust the deb model with the one compartment toxico-kinetic module to whole body residues provided in Barillet et al (2005) and Barillet et al (2011), we see that at 2100 nM U, uptake should be very important but it hardly is compared to predictions ( fig. 8C).…”
Section: Adult Whole Body Residuesmentioning
confidence: 99%
“…The values of toxicity parameters used to obtain the fits provided for each of the exposed females in this study can be found in ], then the individuals in the 37d-U420 and 15d-1054 as well as in the higher exposure conditions by Barillet et al (2005Barillet et al ( , 2011 would have shrunk to death during the experiment. This is manifestly not the case.…”
Section: Mode Of Action Of Uranium On Females In Reproduction Trialsmentioning
confidence: 99%
See 3 more Smart Citations